EFFECT OF TECHNOPHOBIA ON ATTITUDE TOWARDS E-MARKETING AMONG UNDERGRADUATES IN ENUGU STATE, NIGERIA - Adiukwu, Sunday O. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The contemporary society is increasingly overwhelmed by the growing trend of e-marketing concepts influenced by the increasing innovations in internet technologies. The e-marketing platforms have provided efficient opportunities for consumers to surf the Internet at their convenience while assessing products from numerous online retailers. Indeed, indications suggest that technological skills partly influence consumers' unrestrained passion for the digital marketplace. Therefore, internet anxieties and avoidance could pose a limitation to electronic commerce. Thus, the present study examines the effect of technophobia on attitude towards e-marketing. Two hundred and thirty-five undergraduates from three public tertiary institutions in Enugu state participated in the study. The respondents completed a self-report measure of attitude towards e-marketing and the technology anxiety scale. The simple regression analysis revealed that technophobia is a positive predictor of e-marketing. The implications of the study are discussed.